MODERN ASPECTS OF DIAGNOSTICS AND TREATMENT OF UTERINE FIBROIDS (World Bulletin of Public Health, 2025)
Uterine fibroids are still the most common cause of surgical interventions in gynecology, often leading to the loss of the reproductive organ. The reason for this is the late appeal of women to the doctor after the occurrence of complications, an increase in the size of the uterus and the number of nodes. Numerous studies have shown that today a differentiated approach to the treatment of each woman is necessary, since the widespread use of modern high-resolution ultrasound devices and Doppler sonography allow not only to describe the topography and size of the nodes, but also to determine the nature of the fibroid nodes, their proliferative activity. Uterine fibroids (MF) are formed from smooth muscle cells and affect up to 29% of women aged 15-54 years worldwide. Given the current demographic situation and the increasing trend of pregnancy planning at an older reproductive age every year, an organ-preserving approach to the treatment of MF is becoming a priority.